Aiki ecosystem architecture : uma proposta de arquitetura de ecossistema de software de referência para a área de saúde - Siqueira, Otávio Manoel Pereira (2017)
The rising pressure for enhancing the quality of healthcare services, as well as the need to reduce costs, has led healthcare organizations to increasingly use Information and Communication Technologies (ICT), through the development and the adoption of Healthcare Information Systems (HIS) for different purposes. As a result, the technological environment of these organizations has grown in size and complexity. However, deploying and adopting HIS is not always an easy task. The existence of innumerable patterns, often difficult to use, of legacy systems and a constantly changing environment present major challenges. In addition, the SIS shortage causes that the healthcare organizations cannot create all the solutions they need, making the acquisition of third-party SIS inevitable. Concepts such as Software Architecture and Software Ecosystems can assist in the management of these environments. In this context, this paper presents the AiKi Ecosystem Architecture, a reference ecosystem architecture, which aims to define rules for creating and adopting HIS in healthcare organizations, as well as to establish criteria for the interaction between HIS and people, who are part of this environment. An analysis, through an application, was made at the University Hospital of the Federal University of Sergipe, demonstrating the use and viability of the proposed architecture.